Environmental effects of conversion of petroleum fuel-based motor cars to natural gas vehicles (NGVs) - Jahirul, M.I.; Saidur, Rahman; Masjuki, Haji Hassan; Ahmed, S.; Kalam, M.A. (2007)
In order for saving constrained resources and preservation of environment, natural gas has been found as a proven low cost and low emission alternative fuel to petroleum fuels for all types of motor vehicles. It is being widely used throughout the globe. In Malaysia, still millions of vehicles are plying on use of petroleum fuels. These fuels release huge anti-body and anti-environment gases to the environment. Definitely, this adversely affects the natural ecosystem. In this backdrop, a study is felt important to predict the trend of emissions of these gases released by cars in Malaysia for use of liquid fuels and natural gas between 2006 and 2020. The growth of the demand of vehicles has been considered alongside. The study reveals that the current emission levels of different anti-body gases are huge and these can be significantly reduced by converting liquid fuel based engine into the natural gas based engine.